STUDY OF APPROACHES, METHODS, SOURCES AND INTERPRETATION INSTRUMENTS OF MULLA SADRA - Muâ’ammar, Moh. Nadhir (International Journal of Islamic Khazanah, 2020)
This research is carried out on some uniqueness found in the interpretation of the Al-Qur’an by Mulla Sadra, including: he is a philosopher who is the foremost in interpreting the Al-Qur’an and productive writers who have produced many works. In the hands of Mulla Sadra, the synthesis of the three Islamic intellectual schools, namely Sufi makrifat, philosophy or theosophy, and Shiite theology was finally reached, and directly reflected in the field of esoteric interpretation of the Al-Qur’an. Based on the uniqueness, the author is interested in examining it with the title: "Mulla Sadra’s Interpretation Methodology (Study of Approaches, Methods, Sources and Instruments of Interpretation)". The purpose of this study is to find out and explore the methodology of the interpretation of Al-Quran Mulla Sadra, as well as describe how the approach, methods, sources and instruments of interpretation of the Al-Quran that he initiated. And to find out and criticize the application of the interpretation methodology of Al-Quran Mulla Sadra in its interpretation product. This type of research is a library research based on the book of Tafsir al-Qur’an al-Karim as a primary data source. Based on this research, we can draw the conclusion that Sadra’s work is a combination of approaches and interpretive methods that have developed in the Islamic world. The advantage is that it combines two approaches, namely f irfani and philosophy. This is then considered a bridge from the different interpretive traditions in the Islamic world